Epicurus and the Singularity of Death : Defending Radical Epicureanism - Suits, David B. (Bloomsbury Publishing Plc, 2020)
Intro -- Title Page -- Copyright Page -- Contents -- Acknowledgments -- Chapter 1: The Epicurean View of Death -- 1 The argument -- 2 Old habits -- 3 Deprivation -- 4 Death is not a solution -- 5 Length of life -- 6 Death is of no concern -- Chapter 2: Radical Epicureanism -- 1 The argument, again -- 2 To thanatize -- 3 Wills -- 4 Time -- 5 Continuity -- Chapter 3: Premature Death and the Complete Life -- 1 The challenge -- 2 Rescue attempts -- 3 Critique of Rescue arguments -- 4 Conclusion and anticipation -- Chapter 4: Counterfactual Comments -- 1 Causal explanation -- 2 The fog of were -- 3 Two kinds of counterfactuals -- Chapter 5: Death and Deprivation -- 1 Death can be bad -- 2 Ordinary deprivation -- 3 Death cannot be an ordinary deprivation -- 4 The Fallacy of Misplaced Contingency -- 5 Could death be a special kind of deprivation? -- 6 Postmortem well-being -- 7 How death can be bad -- Chapter 6: A Critique in Four Dimensions -- 1 Silverstein's view -- 2 Understanding the "how" -- 3 VCF revisited -- Chapter 7: Killing -- 1 The right to life -- 2 The Essential Potential of an "Instead" Condition (EPIC) Argument -- 3 The Usual Requirement of Unwanted Situations (URUS) Argument -- 4 Objections and replies. -- 5 The significance of suffering -- 6 Policy -- 7 Abortion -- 8 Reorientation -- Chapter 8: Immortality -- 1 Kinds of immortality -- 2 Conditional immortality -- 3 Lucretius's replacement argument -- 4 Evolution -- 5 Avoiding pain -- 6 Cherished values -- 7 Boredom -- 8 Pointlessness -- 9 Ersatz immortality -- Chapter 9: Will He Nill He -- 1 Problems -- 2 Contracts and promises -- 3 Friendship -- 4 Wills -- 5 Callousness and indifference -- 6 Attenuated transitivity of concern -- Chapter 10: Suicide -- 1 Some ethical issues in suicide -- 2 Some prudential issues in suicide -- 3 A note on duration -- 4 How to solve the problem?.